2022
DOI: 10.1590/0102-311xen144521
|View full text |Cite
|
Sign up to set email alerts
|

High dietary calcium intake and low adiposity: findings from a longitudinal study in Brazilian adolescents

Abstract: Epidemiological studies have supported the hypothesis that dietary calcium intake is protective for adiposity. This study aimed to estimate the association of dietary calcium with adiposity indicators during adolescence. This is a cohort study with high school adolescents (n = 962) from selected schools of the Metropolitan Region of Rio de Janeiro, Brazil, which were followed from 2010 to 2012. Calcium intake was assessed by a validated self-reported food frequency questionnaire. Cross-sectional and longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…The diversity between race/ethnicity may be related to different dietary habits, lifestyles, and economic levels [ 37 ]. Studies have shown that overweight and obesity are one of the important factors affecting HBV infection, and high dietary calcium intake can reduce obesity to some extent, thereby reducing the risk of infection [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diversity between race/ethnicity may be related to different dietary habits, lifestyles, and economic levels [ 37 ]. Studies have shown that overweight and obesity are one of the important factors affecting HBV infection, and high dietary calcium intake can reduce obesity to some extent, thereby reducing the risk of infection [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in 244 females from 12 to 19 years, an inverse correlation between Ca intake and BMI, WC, HC, and W/H ratio, was found. In a cohort of 962 school adolescents, authors suggested that low Ca intake increases adiposity among adolescents [23]. In addition, in the IDEFICS study, in 6696 children (51%f boys, 6 ± 1.8 years), authors found an inverse association between total Ca intake and BMI, WC, sum of skinfolds (SS), and FM index in boys, and only the SS and FM index in girls [99].…”
Section: Calciummentioning
confidence: 98%
“…Body fat percentage [(BF%: fat mass/total weight) × 100] was calculated; the excess body adiposity was ≥25% for boys and ≥ 30% for girls. The fraction of body fat was estimated using the fat mass index [FMI = fat mass/height 2 (kg/m 2 )] and the free fraction of body fat with the fat-free mass index [FFMI = fat-free mass/height 2 (kg/m 2 )] [23]. Basal energy expenditure (EE) or at rest (REE) was measured with Indirect Calorimetry (IC) in fasting, using a canopy system under standardized conditions [Deltarac II (Datex-Ohmeda.…”
Section: Assessment Of Phenotypical Characteristicsmentioning
confidence: 99%
“…In addition to gestational weight gain (GWG), prepregnancy BMI and breastfeeding practices, energy intake (Brewer et al, 1989; Hediger et al, 1997; Kac et al, 2004; Montpetit et al, 2012), that are recognized to affect body weight and/or body composition changes during the postpartum period, it is possible that calcium intake favor loss of weight and/or fat mass. An habitually low calcium intake appears to contribute to fat mass and/or weight accumulation in both adults (Lu et al, 2021) and adolescents (Moraes et al, 2022). There is also evidence that increasing calcium intake, combined or not with additional vitamin D, results in weight and/or fat loss (Subih et al, 2018; Zemel et al, 2004; Zhu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%